Study on the effects of shear stress on the invasion of circulating tumour cells - Ong, Shi Min (2015)
Cancer metastasis is responsible for approximately 90% human cancer-related death. It involves a series of complex metastasis-related signalling pathway that includes local tumour cell invasion into the blood stream, which are believed to adhere on the ECM and then extravasate into distal sites. While in the circulation, the cancerous cells continuously experience shear stress in the interstitial fluid flow which cause them to be lethally damaged in the microvasculature. In order to survive, they have to adhere to the vessels wall, invade across the endothelium to escape from the shear stress. Surviving in the bloodstream is a rate-limiting step for the metastasis, thus the ability to invade the endothelium to escape from shear stress plays a vital role in the formation of a secondary tumour. In this final year project, it aims to research on the invasiveness of the circulating tumour cells (CTCs). A microfluidic system which can generate an oscillatory shear flow in a circulatory channel was used to mimic the microenvironment of CTCs. Experimental comparisons between CTCs and control MDA-MB-231 cells with C3 (denoted as 231-C3) group were conducted using zymography and transwell invasion assay to evaluate the effect of shear stress on the invasion potential of the CTCs. It was observed that 231-C3 cells that experienced the microenvironment of CTCs generally expressed greater activities of MMP-9 and MMP-2 and exhibit higher invasive potential as compared to normal tumour cells.